Incidence rate and associated patient characteristics of liver disease in Wales 2004–2022: a retrospective population-scale observational study - Ashley Akbari; Andrew Yeoman; Haroon Ahmed; Jingwei Gao; Aled Davies; Thomas Peter Ignatius Pembroke (BMJ Open)
Objective To describe the incidence and key demographic, socioeconomic and clinical characteristics of individuals with liver disease in Wales.Design and setting This study is designed as a retrospective observational study that linked data of anonymised identified individuals from primary, secondary care and mortality data from the Secure Anonymised Information Linkage (SAIL) Databank in Wales.Participants All Welsh residents who registered with a SAIL-contributing general practitioner (GP) and diagnosed with liver disease from 2004 to 2022.Primary and secondary outcome measures Our primary outcome is the annual age-standardised incidence rate of liver disease. Secondary outcome is the numbers and frequencies of underlying aetiology and the associated comorbidities.Results Between 2004 and 2022, 111 098 individuals received a diagnosis of liver disease in Wales and were included in this study. The incidence of liver disease increased threefold during the study period (97.7 per 100 000 inhabitants in 2004 to 316.2 per 100 000 inhabitants in 2022). A total of 79 992 individuals (72%) entered the cohort with the underlying aetiology of liver disease, including alcohol-related liver disease, non-alcoholic fatty liver disease (NAFLD), viral hepatitis, metabolic, haemochromatosis and autoimmune liver diseases. NAFLD has contributed to most of the change in incidence.Conclusions We observed increasing incidence rates of liver disease in Wales, with NAFLD showing a particularly sharp increase and frequently identified as an underlying condition. A better understanding of the incidence of liver disease is the first step towards effective prevention, early detection and targeted intervention to improve patient outcomes.